Brazil [in Agricultural Extension] - Bergamasco, Sonia Maria Pessoa Pereira; Borsatto, Ricardo Serra; Thomson, Carolina Rios; Davis, Kristin E.; Babu, Suresh Chandra (International Food Policy Research Institute, 2020)
This chapter examined perceptions of family farmers and extensionists regarding extension services resulting from the agricultural extension policy in Brazil. The results show that participatory methodologies should guide service delivery, that a agroecological principles should be the technical guideline, and that family farming should be the primary beneficiary, receiving free and universal (and pluralistic) services.